Optimization of Student Learning Activities of SMA Negeri 1 Pulau Banyak in Islamic Education Learning through the STAD Type Cooperative Model - Gusanti, Henni; Abrar, Yudi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education subjects on the material of Islamic Law on Maintaining Honesty as a Reflection of Personality through the application of the Student Teams Achievement Division (STAD) cooperative learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were class IX of SMA Negeri 1 Pulau Banyak, Aceh Singkil Regency, in the 2023/2024 academic year. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The results of the study showed that there was a significant increase in student learning completeness after the implementation of the STAD learning model. Before the implementation of the STAD model, the level of student learning completeness only reached 13.04%. After cycle I, completeness increased to 73.91%, and in cycle II it reached 95.65%. These findings prove that the application of the STAD type cooperative learning model is effective in improving student learning activities and outcomes, especially in understanding and applying the values ​​of honesty as part of the character that must be possessed. Thus, the STAD model can be used as a relevant learning strategy in teaching Islamic Religious Education at the secondary school level.